Extra-pulmonary vein driver mapping and ablation for persistent atrial fibrillation in obese patients. Issue 5 (1st December 2020) - Hu, Xiaofeng; Jiang, Weifeng; Wu, Shaohui; Xu, Kai; Zhang, Daoliang; Zhang, Yu; Liu, Xu; Qin, Mu
Abstract: Aims: The aim of this study was to determine whether driver ablation effectively treats persistent atrial fibrillation (AF) in obese patients. Methods and results: We randomly assigned 124 persistent AF obese patients to two groups, one undergoing conventional ablation ( n = 62) and the other undergoing driver ablation ( n = 62). Sixty-two non-obese patients with persistent AF undergoing driver ablation served as matched controls. Bipolar electrogram dispersion was analysed for driver mapping. Epicardial adipose tissue (EAT) volume was measured using cardiac computed tomography. Obese patients had a higher proportion of driver regions in the posterior wall (56.5% vs. 32.3%, P = 0.007). Driver complexity, measured as the average number and area of driver regions, was higher in the obese group than in the non-obese group (3.5 ± 1.0 vs. 2.9 ± 0.9, P < 0.001; 15.5% ± 4.2% vs. 9.8 ± 2.6%, P < 0.001, respectively). Left atrial EAT volume correlated better with the proportion of area of driver regions than did body mass index (BMI) and total EAT (BMI: r 2 = 0.250, P < 0.001; total EAT: r 2 = 0.379, P < 0.001; and left atrial EAT: r 2 = 0.439, P < 0.001). The rate of AF termination was significantly higher in the driver ablation group than in the conventional ablation group (82.9% vs. 22.8%, P < 0.001). During the follow-up period of 16.9 ± 6.5 months, patients in the driver ablation group had significantly better AF-free survival (91.91% vs. 79.0%, log rank test, P = 0.026) and AF/atrial tachycardia-free survival (83.9% vs. 64.5%, log rank test, P = 0.011) than did patients in the conventional ablation group. Conclusion: Obesity is associated with increased driver complexity. Driver ablation improves long-term outcomes in obese patients with persistent AF.